1094 Depression Is Not Associated With The Presence Of Or The Severity Of Obstructive Sleep Apnea: Retrospective Study Of 841 Polysomnography Subjects. (27th May 2020) - Im, K; Kim, L; Immen, R
Abstract: Introduction: Both depression and obstructive sleep apnea (OSA) are very common medical conditions. Studies showed a co-occurrence of depression and OSA with a higher prevalence of one if the other is present. However, there is relative paucity of studies assessing the rate of depression based on the OSA severity. Methods: Retrospective analysis of data collected from patients undergoing polysomnography (PSG) at an academic sleep disorders center was performed. A total of 841 subjects were included and stratified into four groups using AHI. A Chi-square analysis was applied to assess the association of varying levels of AHI and the presence of depression. Results: Although a significant proportion of patients with AHI greater than 5 endorsed depression (60/165 in group with AHI 15 or greater and 115/278 in group with AHI between 5 and 15), this finding was also replicated in patients with AHI less than 5 (86/202 in AHI between 1 and 5 and 88/196 in those with AHI less than 1). As there was significant difference in rate of depression among women (54.1%) and men (26.1%) (p <0.0001), Chi-square analysis was performed for the rate of depression based on the level of AHI, adjusted for gender. In women the rate of depression from the most severe AHI to less severe AHI group were 0.48, 0.53, 0.60, and 0.53 respectively and in men it was 0.30, 0.27, 0.20, and 0.27 respectively, with no statistical difference between any groups. Conclusion: Among patients who seek PSG assessment, depression appears to be more prevalent than the general public. Rate of depression is much higher among women than men in this group. However, the presence of OSA or severity of OSA does not have any correlation with the rate of depression in both women and men. These findings might be suggestive of the complexity of the association between depression and OSA. One limitation of this study is the dichotomous nature of depression (presence or absence of). The finding from this study warrants a future study utilizing a numerical rating scale of depression for severity measure to correlate it with the severity of OSA. Support: NA.